The immune system: an overview - innate immunity - Pillai, Shiv (Henry Stewart Talks, 2019)
Background on immunity research, Overview of the inflammation process, Inflammation and leukocyte recruitment, Components of the innate immune system, Bacterial PAMPs and innate receptors, Transition from innate immunity to adaptive immunity